2006
DOI: 10.1121/1.2357708
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in the sensitivity to pitch direction

Abstract: It is commonly assumed that one can always assign a direction-upward or downward-to a percept of pitch change. The present study shows that this is true for some, but not all, listeners. Frequency difference limens (FDLs, in cents) for pure tones roved in frequency were measured in two conditions. In one condition, the task was to detect frequency changes; in the other condition, the task was to identify the direction of frequency changes. For three listeners, the identification FDL was about 1.5 times smaller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 23 publications
(14 reference statements)
5
73
0
Order By: Relevance
“…Based on earlier findings, which suggest that the human auditory system contains neural populations that are selectively sensitive to the direction of small frequency changes ͑Demany and Ramos, 2005; Demany et al, 2009b͒ Semal andDemany, ͑2006͒ proposed that such frequency-shift detectors ͑FSDs͒ may not respond to small shifts in the brains of direction-impaired listeners. The result that insensitivity to pitch-change direction is greatly reduced or eliminated when wide frequency roving is not used suggests either that this explanation is incorrect, or that when the stimuli are not roved widely in frequency, listeners' ability to identify pitchchange direction no longer relies on FSDs.…”
Section: B Implications For the Origin Of The Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on earlier findings, which suggest that the human auditory system contains neural populations that are selectively sensitive to the direction of small frequency changes ͑Demany and Ramos, 2005; Demany et al, 2009b͒ Semal andDemany, ͑2006͒ proposed that such frequency-shift detectors ͑FSDs͒ may not respond to small shifts in the brains of direction-impaired listeners. The result that insensitivity to pitch-change direction is greatly reduced or eliminated when wide frequency roving is not used suggests either that this explanation is incorrect, or that when the stimuli are not roved widely in frequency, listeners' ability to identify pitchchange direction no longer relies on FSDs.…”
Section: B Implications For the Origin Of The Impairmentmentioning
confidence: 99%
“…Clearly these experiments require listeners to be-and indeed demonstrate that they often are-sensitive to the direction or sign of very small frequency changes. However, three more recent studies have suggested that in certain circumstances some listeners can detect the presence of a small frequency difference, but are unable to identify the direction of the resulting percept ͑Johnsrude et al, 2000; Tramo et al, 2002;Semal and Demany, 2006͒. Two of the studies cited above involved listeners with cortical lesions. Johnsrude et al ͑2000͒ tested patients with unilateral temporal lobe excisions and healthy controls using two frequency discrimination tasks: a two-interval, twoalternative forced-choice ͑2I-2AFC͒ task similar to those used in classic studies of frequency discrimination, and a same-different ͑SD͒ task in which the second tone was equiprobably identical to or higher in frequency than the first tone.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the participant is now asked to indicate whether the pair containing one A and one B stimulus was AB or BA. Although it is superficially similar to the basic 4IAX paradigm, the 4IAX, ABversus-BA paradigm involves a substantially different underlying decision strategy and a completely different relationship between d′ and Pc (Micheyl & Dai, 2009;Semal & Demany, 2006). For these two dual-pair paradigms, Pc can be determined following an approach similar to the one that we used for the two-interval same-different paradigm.…”
Section: Dual-pair Paradigmsmentioning
confidence: 99%
“…In one version-namely the basic dual-pair paradigm, which is commonly abbreviated 4IAX (for four-interval, samedifferent)-the task of the participant is to indicate which pair contains stimuli that are different (AB or BA vs. AA or BB). This version of the paradigm is useful in experiments that aim to measure performance in stimulus discrimination, or change detection Semal & Demany, 2006). In the second version-namely the 4IAX, AB-versus-BA paradigmthe exact same stimulus design can be used to explore a different ability of the participant, the ability to identify the direction of changes (i.e., AB vs. BA); all that the experimenter needs to do is to change the instructions.…”
Section: Dual-pair Paradigmsmentioning
confidence: 99%
See 1 more Smart Citation